Blood Т-cell subpopulations dynamics in asthma under suspended particulate load in vitro - E. V. Kondratyeva; T. I. Vitkina; S. I. Kolesnikov (Acta Biomedica Scientifica)
Background. Bronchial asthma (BA) is characterized by dysregulation of the adaptive immune response. A significant contribution to pathological processes in urban environments is made by air pollution with solid suspended particles (HDPE). However, the expression of cytokine (interleukin (IL) 4, 6) and toll-like receptors (TLR) CD8+ cells in BA patients and their dynamics under exposure to atmospheric microtoxicants practically have not been studied. The aim. To determine the features of expression of IL-4R, IL-6R, TLR2, and TLR4 in CD8+ cells in BA of varying severity and under the influence of solid suspended particles of atmospheric air. Materials and methods. The study included 244 patients with asthma, 60 conditionally healthy individuals. Loading with simulated atmospheric suspensions was performed at a dose of 1 microgram (µg) of suspension per 1 ml of blood. The expression of IL-4R, IL-6R, TLR2, and TLR4 on CD8+ cells was analyzed by flow cytofluorometry. Statistical processing of the results was performed in the program “STATISTICA 10.0”. The critical significance level (p) for testing statistical hypotheses was assumed at p < 0.05. Results. The main differences in cell signaling were observed between the group with partially controlled moderate BA and the control group. The expression of IL-4R is particularly strongly increased – by 217 % (p < 0.001), TLR4 – by 103 % (p < 0.001). The same group of patients is characterized by the greatest significance of differences in T-cytotoxic cells in comparison with the group of patients with mild bronchial asthma. IL-4 receptor expression on T-cytotoxic cells increased by 160 % (p < 0.001), TLR4 – by 108 % (p < 0.001). Conclusion. The intensification of receptor expression is observed with an increase in the severity of the disease. The expression of IL-4R and TLR4 changes most intensively in T-cytotoxic cells IL-4R and TLR.